Protocol for the RT Prepare Trial: a multiple-baseline study of radiation therapists delivering education and support to women with breast cancer who are referred for radiotherapy - Halkett, Georgia; O'Connor, Moira; Aranda, S.; Jefford, M.; Spry, N.; Shaw, T.; Moorin, Rachael; Schofield, P. (B M J Group, 2014)
Introduction: There is limited evidence to guide the preparation of patients for radiotherapy. This paper describes the protocol for an evaluation of a radiation therapist led education intervention delivered to patients with breast cancer in order to reduce psychological distress.